Secondary transfer effects of intergroup contact alternative accounts and underlying processes.[article]. - Taush, Nicole
Although intergroup contact is one of the most prominent interventions to reduce prejudice, the generalization of contact effects is still a contentious issue. This research further examined the rarely studied secondary transfer effect (STE; Pettigrew, 2009), by which contact with a primary outgroup reduces prejudice towards secondary groups that are not directly involved in the contact. Across 3 cross-sectional studies conducted in Cyprus(N=1,653_, Northern Ireland (N=1,973), and Texas (N=275) and 2 longitudinal study conducted in Northern Ireland (N=411), the present research sought to systematically rule out alternative accounts of the STE and to investigate 2 potential mediating mechanisms (ingroup reappraisal and attitude generalization). Results indicated that, consistent with the STE, contact with a primary outgroup predict attitudes toward secondary outgroups, over and above contact with secondary outgroup, socially desirable responding, and prior attitudes. Mediation analyses found strong evidence for attitudes generalization but only limited evidence for ingroup reappraisal as an underlying process. Two out of 3 tests of a reverse model, where contact with the secondary outgroup predicts attitudes toward the primary outgroup, provide further evidence for an indirect effect through attitude generalization. Theoretical and practical implications of these results are discussed, and directions for future research are identified. -- (from the author)
Keywords: Intergroup contact; prejudice reduction; Secondary transfer effect; Attitude generalization; Ingroup reappraisal